Randomized controlled and double‐blinded study of Caphosol versus saline oral rinses in pediatric patients with cancer. Issue 10 (29th July 2020) - Immonen, Egle; Aine, Liisa; Nikkilä, Atte; Parikka, Mataleena; Grönroos, Marika; Vepsäläinen, Kaisa; Palmu, Sauli; Helminen, Mika; Peltomäki, Timo; Lohi, Olli
Abstract: Background: Oral mucositis (OM) is a significant side effect of cancer treatment. The purpose of this study was to compare topically administered Caphosol to saline rinses in the prevention of mucositis in pediatric cancer patients. Procedure: A controlled, double‐blinded, and randomized clinical crossover study recruited patients between 2 to 17.99 years of age who were diagnosed with a malignancy and were receiving either high‐dose methotrexate (≥1 g/m 2 ), anthracycline, or cisplatin chemotherapy (NCT0280733). All patients received two 7‐day cycles of the mouth rinses; that is, one cycle of Caphosol and one cycle of saline in a randomized order. Oral changes and symptoms were evaluated using the World Health Organisation (WHO) toxicity scale and the Children's International Mucositis Evaluation Scale (ChIMES). The primary endpoint was the frequency and severity of OM and oral symptoms. Results: A total of 56 patients were recruited to the study, of whom 45 were randomized with a median age of 6.5 years (range 2.1‐17.1 years). No cases of severe OM were observed. Grade ≥ 3 oral symptoms were present at least once in six (13%) patients during the Caphosol cycle and 13 (29%) patients during the saline cycle ( P  = .12). The peak of symptom scores was evident at around day 4‐7 after administration of the chemotherapy with no marked differences between the rinse solutions. Multivariable regression analysis did not indicate a benefit of using Caphosol over the saline solution. Conclusions: No difference in prevention of oral mucositis was observed between the use of Caphosol or saline rinses.